A Stirling engine for use with lower quality fuels. (1st May 2015) - Paul, Christopher J.; Engeda, Abraham
Abstract: A Stirling engine for use with lower quality fuels was designed. The design is a derivative of the GPU-3 (ground power unit-3), modified to be used with a lower combustion gas temperature (900 °C). It is to be used in a generator set producing 5 kWe. The engine model used is based off of the ideal adiabatic model with decoupled loss mechanisms. Single-cylinder and two-cylinder engines were analyzed using a preheater and CGR (combustion gas recirculation). The analysis shows that the external surface area of the heater plays a very important role in determining the system performance. Maximum system efficiency was found by significantly increasing the surface area at the expense of increased dead volume. A single-cylinder configuration was found to offer the best combination of system efficiency (23.6%) and manufacturing cost. Highlights: Effect of combustor gas temperature on original GPU-3 is analyzed. Increasing the heater surface area allows the system to produce more power. There is an engine swept volume that maximizes system efficiency. Multiple cylinder engines can achieve higher efficiencies than single cylinder ones. Adding combustion gas recirculation improves system efficiency.